3D Printing as a Teaching Tool in Veterinary Medicine: Feline Ocular Model for Ultrasound Training - Cristiana A.C. Lima; Ana I. Filipe; Lisa A. Mestrinho (Journal of Veterinary Medical Education, 2026)
Abstract A three-dimensional (3D) clinical simulation model was developed for ocular ultrasonography training, and its pedagogical potential was evaluated. Model design was based on computed tomography data of feline skulls, which were processed and segmented using specialized 3D modeling software. During this process, Standard Tessellation Language (STL) files were produced, corresponding to the three main model components: a feline skull and two eyeballs, one representing normal anatomy and the other simulating a total retinal detachment. All components were printed using a stereolithography printer. Rigid resin was used to print the skull and flexible resin for the eyeballs. Each eyeball was filled with a medical-grade gel with physical and acoustic properties like those of real feline eye. The printing and assembly stages resulted in reduced production costs and moderate reproducibility. Following initial fidelity validation by an experienced veterinary ultrasonographer, the model's pedagogical potential was assessed by veterinary students and practicing veterinarians during a structured training session, followed by the completion of a qualitative survey. Overall feedback was positive, with participants reporting acceptable fidelity, ease of use, and perceived improvements in manual dexterity and technical learning. Statistically significant associations were observed between academic degree and performance scores and between prior practical experience in ocular ultrasonography and perceived task ease. The feline ocular model represents a cost-effective, safe, and accessible educational tool with satisfactory sonographic fidelity.